Engaging nurses in research and quality improvement is associated with higher job satisfaction and lower rates of unscheduled time off work: A pilot study. (June 2020) - Fitzpatrick, Colin; Buckingham, Tracey; Merrell, Jayne; McCooey, Chris; Richardson, Daniel
We aim to identify associations that may help support strategies to increase job satisfaction and reduce unscheduled time off work for nurses. Given current concerns regarding nursing workforce and retention, it is vital we identify strategies and factors which maintain job satisfaction, support staff retention and reduce unscheduled time off work. As part of a quality improvement project, we conducted and distributed an online anonymous survey. Likert scales were used to measure job satisfaction, perceived quality of care, wellbeing, and unscheduled time off work. We explored participation in project work of any kind in the preceding 12 months, and captured nursing experience and current area of practice (inpatient/outpatient). A total of 350 complete responses were analysed. Nurses engaged in research or Quality Improvement Projects (QIPs) were more likely to have higher perceived levels of patient care (p = 0.0001), wellbeing (p = 0.0001) and job satisfaction (p = 0.0001) and reported lower levels of unscheduled time off work (p = 0.0001). Nurses engaged in research or quality improvement projects reported higher levels of job satisfaction, wellbeing, perceived higher levels of care in their workplace, and had lower levels of unscheduled time off work. We suggest that involving nurses in research/QIPs may improve workforce instability and job satisfaction.